High-Involvement Management: Participative Strategies for Improving Organizational PerformanceHigh-Involvement Management: Participative Strategies for Improving Organizational Performance, by LawlerEdward E.III.. San Francisco: Jossey-Bass. 1986, 252 pp., cloth - Ross, Steven C.; Koys, Daniel J. (Academy of Management Review, 1987)
The article reviews the book ?High-Involvement Management: Participative Strategies for Improving Organizational Performance,? by Edward E. Lawler III.